The influence of the methods of main tillage on the yield of maize hybrids in the conditions of the Left Bank Forest Steppe - Hanhur, V.; Marenych, M.; Yeremko, L.; Shostia, A.; Puzyr, D.; Kyrlytsia, A. (Scientific Progress & Innovations, 2023)
Corn (Zea mays L.) due to important economic and valuable properties has a wide range of uses, including food and fodder as well as industrial use (raw materials for bioethanol and biogas production). The technology of primary tillage is an important agrotechnical methods for regulating the level of realization of the genetic potential of corn productivity. The studies conducted on the experimental field of the Poltava State Agricultural Research Institute named after M. I. Vavilov during 2022‒2023 found that the early-ripening hybrid Kvitnevyi 187 MV had the lowest pre-harvest grain moisture content when surface tillage was carried out to a depth of 8‒10 cm (16.8 %). When the hybrid was grown on the basis of flat-cut tillage and plowing to a depth of 25-27 cm, the grain moisture content increased by 0.4 and 1.7 % (absolute), respectively. The grain of the mid-early ripening hybrid Orzhytsia 237 MV better released moisture on the background of plowing to a depth of 25‒27 cm, and in the variants of moldboardless tillage, an increase in the moisture content by 0.8‒1.2 % (absolute) was observed. A similar tendency was found in the middle-ripening hybrid Bystrytsia 400 MV. According to the results of the research, it was found that the early-ripening hybrid Kvitnevyi 187 MV and the medium-early ripening hybrid Orzhytsia 237 MV formed the highest and almost the same yield (7.59 and 7.45 t/ha, respectively) with plowing and flat-cutting tillage to a depth of 25‒27 cm. A significant decrease in the yield of these corn hybrids was observed with surface tillage by 8‒10 cm. The difference in yield compared to the best tillage options was 0.26‒0.40 and 0.21‒0.23 t/ha, respectively. The medium-ripening hybrid Bystrytsia 400 MV formed the maximum yield (7.91 t/ha) when carrying out shelf cultivation to a depth of 25‒27 cm. In the case of changing plowing for loosening the soil with flat-cutting tools to a similar depth or carrying out surface tillage to a depth of 8‒10 cm, a significant decrease in grain yield was noted, respectively, by 0.64 and 0.95 t/ha or 8.1 and 12.0 %.